Error resilient image coding and smart post-processing error concealment for wireless image transmission - Ong, Keng-Khai; Lee, Yew-San; Lee, Chen-Yi (2002 IEEE International Conference on Acoustics, Speech, and Signal Processing, 2002)
In recent years, there has been a huge growth in the areas of multimedia and wireless communications. Image transmission through bandwidth limited and high bit error rate wireless channel requires both compression and error resilient capabilities. We propose an error resilient image coding and smart error concealment schemes for DCT-based [1] image compression, such as JPEG and MPEG standards. It can successfully prevent error propagation between the transmitted data blocks with little overhead. In addition, we present a novel post-processing error concealment scheme, called Smart-IDCT (SIDCT). It tries to retain error free low frequency DCT information and discarding highly suspicious high frequency information. Then, we can retrieve low-resolution information instead of totally corrupted image block during the decoding process. The required computation power is much less than conventional error detection and correction schemes. Simulation results show that the overhead of ERIC is about 5% compared to the JPEG sequential DCT-based mode without restart marker. With the SIDCT post-processing, it can achieve excellent image quality (PSNR=31.78dB).